The Application of The Discovery Learning Model in Wave Concepts to Enhance High School Students’ Cognitive and Problem-Solving Skills - Ridwan Assidik; Parlindungan Sinaga; Muhamad Gina Nugraha (Equator Science Journal, 2026)
This study aims to implement the Discovery Learning model to improve the cognitive abilities and problem-solving skills of high school students on the topic of waves. The research method used is pre-experimental with a one-group pretest-posttest design. Research instruments include objective tests to measure cognitive abilities and essay tests to measure problem-solving skills. The results show that the application of the Discovery Learning model provides a significant contribution to student learning outcomes. Cognitive ability improved with an average N-Gain value of 0.76, which is classified in the High category. Meanwhile, problem-solving skills also increased with an average N-Gain value of 0.79, also in the High category. Overall, the Discovery Learning model is effective in improving the mastery of cognitive concepts; however, more intensive guidance and continuous habituation are required to optimize students' systematic problem-solving skills.